2001
DOI: 10.1080/00207160108805080
|View full text |Cite
|
Sign up to set email alerts
|

On benchmarking functions for genetic algorithms

Abstract: This paper presents experimental results on the major benchmarking functions used for performance evaluation of Genetic Algorithms (GAS). Parameters considered include the effect of population size, crossover probability, mutation rate and pseudorandom generator. The general computational behavior of two basic GAS models, the Generational Replacement Model (GRM) and the Steady State Replacement Model (SSRM) is evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(156 citation statements)
references
References 6 publications
3
143
0
2
Order By: Relevance
“…At a saddle, the Hessian has both positive and negative character. The existence of landscape saddles has practical significance for OCT optimizations, since their presence may influence searches with a gradient algorithm [110,115] or even hinder the convergence efficiency of global stochastic algorithms [116]. The topic assessed in this paper is the role of saddles in seeking optimal controls, as reflected in the performance of a gradient-based algorithm which was chosen due to its sensitivity to landscape saddle features.…”
Section: A Backgroundmentioning
confidence: 99%
“…At a saddle, the Hessian has both positive and negative character. The existence of landscape saddles has practical significance for OCT optimizations, since their presence may influence searches with a gradient algorithm [110,115] or even hinder the convergence efficiency of global stochastic algorithms [116]. The topic assessed in this paper is the role of saddles in seeking optimal controls, as reflected in the performance of a gradient-based algorithm which was chosen due to its sensitivity to landscape saddle features.…”
Section: A Backgroundmentioning
confidence: 99%
“…The landscape topology has practical significance for quantum control optimizations, since local optima may trap gradient searches and can even affect the efficiency of genetic algorithms [150]. When the landscape lacks local traps, on the other hand, several OCT studies consisting of thousands of numerical simulations have shown that gradient searches can quickly locate globally optimal controls [130,[151][152][153].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the essential characteristics of these functions are that the functions should be multimodal or unimodal in nature, the function should be nonseparable, and moreover, the functions should lag in the global structure. By keeping these virtues in consideration, benchmarking of the variants is done on five unimodal and five multimodal shifted and biased benchmark functions [31][32][33]. In the standard benchmark functions, the minima lies at zero; however, in multimodal functions, multioptima (local) can exist.…”
Section: Simulation and Resultsmentioning
confidence: 99%